Show me your networks and i'll tell you your future: entrepreneurial networks and SME performance - Elia John (Cogent Business & Management, 2024)
The main objective of this study is to examine how entrepreneurial networks influence Small- and Medium-sized Enterprises (SMEs) nonfinancial performance. By exploring nonfinancial dimensions of SME performance influenced by entrepreneurial networks, the study contributes to the development of a more comprehensive theoretical understanding of the role of networks in SME success. Entrepreneurial networks involve social, business, and supporting networks, while nonfinancial performance encompasses customer perspective, internal business processes, and learning and growth. A study used a survey method to collect primary data from 278 SMEs. To assess the impact of entrepreneurial networks on SME performance, a study employed multiple linear regression models while considering the influence of control variables such as the entrepreneur's age, sex, and firm size. Overall, the findings indicate that social networks have a significant positive relationship with customer perspective, business networks and supporting networks are statistically significant and positively associated with internal business processes, and supporting networks are positively and significantly related to learning and growth. This implies that, SMEs with owners who are embedded in a web of entrepreneurial networks have a strong chance of achieving success in their businesses beyond financial measures. The study contributes by extending the body of knowledge regarding Resource Dependence Theory (RDT) and presenting valuable evidence for understanding the importance of networking to SME performance in a context of developing countries such as Tanzania. It also provides insights to policy makers to design policies and programs that foster the creation and maintenance of supportive network environments for SMEs.
Keywords: 650; Entrepreneurial networks; SMEs; SME performance; non-financial performance